Validation of a commercial insulated isothermal PCR-based POCKIT test for rapid and easy detection of white spot syndrome virus infection in Litopenaeus vannamei. - Yun-Long Tsai; Han-Ching Wang; Chu-Fang Lo; Kathy Tang-Nelson; Donald Lightner; Bor-Rung Ou; Ai-Ling Hour; Chuan-Fu Tsai; Cheng-Chi Yen; Hsiao-Fen Grace Chang; Ping-Hua Teng; Pei-Yu Lee (PLoS ONE, 2014)
Timely pond-side detection of white spot syndrome virus (WSSV) plays a critical role in the implementation of bio-security measures to help minimize economic losses caused by white spot syndrome disease, an important threat to shrimp aquaculture industry worldwide. A portable device, namely POCKIT™, became available recently to complete fluorescent probe-based insulated isothermal PCR (iiPCR), and automatic data detection and interpretation within one hour. Taking advantage of this platform, the IQ Plus™ WSSV Kit with POCKIT system was established to allow simple and easy WSSV detection for on-site users. The assay was first evaluated for its analytical sensitivity and specificity performance. The 95% limit of detection (LOD) of the assay was 17 copies of WSSV genomic DNA per reaction (95% confidence interval [CI], 13 to 24 copies per reaction). The established assay has detection sensitivity similar to that of OIE-registered IQ2000™ WSSV Detection and Protection System with serial dilutions of WSSV-positive Litopenaeus vannamei DNA. No cross-reaction signals were generated from infectious hypodermal and haematopoietic necrosis virus (IHHNV), monodon baculovirus (MBV), and hepatopancreatic parvovirus (HPV) positive samples. Accuracy analysis using 700 L. vannamei of known WSSV infection status shows that the established assayhassensitivity93.5% (95% CI: 90.61-95.56%) and specificity 97% (95% CI: 94.31-98.50%). Furthermore, no discrepancy was found between the two assays when 100 random L. vannamei samples were tested in parallel. Finally, excellent correlation was observed among test results of three batches of reagents with 64 samples analyzed in three different laboratories. Working in a portable device, IQ Plus™ WSSV Kit with POCKIT system allows reliable, sensitive and specific on-site detection of WSSV in L. vannamei.